2019
DOI: 10.1002/jsfa.10096
|View full text |Cite
|
Sign up to set email alerts
|

Pomegranate juice improves cardiometabolic risk factors, biomarkers of oxidative stress and inflammation in hemodialysis patients: a randomized crossover trial

Abstract: BACKGROUND Pomegranate has antioxidant, cardioprotective and anti‐inflammatory properties. We designed a crossover study aimed at determining if consumption of pomegranate juice (PJ) improves lipid profile and oxidative and inflammatory biomarkers of hemodialysis patients. Forty‐one hemodialysis patients were randomly assigned to one of two groups: PJ‐treated group receiving 100 mL of natural PJ immediately after their dialysis session three times a week and the control group receiving the usual care. After 8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 56 publications
1
53
0
Order By: Relevance
“…Forty-five studies were included in this systematic review, of which 18 were crossover randomised controlled trials (RCT) [27,[33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49], and 27 were parallel RCTs [26,28, (see Table 3). The sample size of both experimental and control group in the interventions ranged from 5 to 63.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Forty-five studies were included in this systematic review, of which 18 were crossover randomised controlled trials (RCT) [27,[33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49], and 27 were parallel RCTs [26,28, (see Table 3). The sample size of both experimental and control group in the interventions ranged from 5 to 63.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The significance of pomegranate health benefits has been revealed by its adaption in several human-based studies ( Table 5). The consumption of pomegranate juice for a period of eight weeks showed beneficial effects on blood pressure, serum triglycerides, high-density lipoprotein cholesterol, oxidative stress and inflammation in hemodialysis patients [85]. In patients with type 2 diabetes, a consumption of 1.5 mL/kg body weight reduced serum erythropoietin level after three hours [86], while a 200 mL/day consumption for six weeks reduced systolic and diastolic blood pressure without affecting the lipid profile [87].…”
Section: Human Studiesmentioning
confidence: 99%
“…Finally, human studies have shown the beneficial effects of the juice on blood pressure, serum triglycerides, high-density lipoprotein (HDL) cholesterol, oxidative stress and inflammation in haemodialysis patients [35]. The juice consumption allows also to reduce the serum erythropoietin level [36] as well as systolic and diastolic blood pressure in patients with type 2 diabetes [37].…”
Section: Juice Composition and Health Propertiesmentioning
confidence: 99%